Penerapan Clustering dalam Data Science Untuk Mengembangkan Keterampilan Analitik di SMK Media Informatika - Eliyani; Muhammad Rifqi; Saruni Dwiasnati (Unity Academy, 2024)
The current and future job market requires a workforce skilled in data science, including analytical techniques such as clustering. With the development of Industry 4.0, skills in data analysis are becoming increasingly important, and education must adapt to meet this need. Increasing data literacy among vocational school students is very important to prepare them to face a world increasingly dominated by data. Analytical skills help students in solving complex problems and making data-driven decisions. Skills in data science encourage innovation and creativity in various fields. Involvement of students so they can use tools and skills to analyze and understand the world around them through data. Clustering is a technique in data science and statistics that is used to group objects or data points that have similar characteristics into groups or clusters. Objective: To equip students with the skills to analyze and interpret data effectively using clustering techniques and provide a strong foundation for students who are interested in continuing their studies in the field of data science or information technology.